Papua New Guinea : 2016 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This 2016 Article IV Consultation highlights that Papua New Guinea is facing headwinds stemming from low commodity prices and is recovering from a major drought; these factors have weighed on economic growth, weakened the external position, and created fiscal challenges. Foreign exchange (FX) remains in short supply, but inflows have recently picked up somewhat. Near-term risks to the outlook are tilted to the downside, as fiscal retrenchment may have a greater impact on the economy than currently expected and the limited availability of FX continues to constrain imports and economic activity. A further drop in commodity prices would weaken the external and fiscal positions.